2019
DOI: 10.1002/ijc.32128
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in RUNX3, AMD1 and MSRA in the methionine metabolic pathway and survival in nonsmall cell lung cancer patients

Abstract: Abnormal methionine dependence in cancer cells has led to methionine restriction as a potential therapeutic strategy. We hypothesized that genetic variants involved in methionine-metabolic genes are associated with survival in non-small cell lung cancer (NSCLC) patients. Therefore, we investigated associations of 16,378 common single-nucleotide polymorphisms (SNPs) in 97 methionine-metabolic pathway genes with overall survival (OS) in NSCLC patients using genotyping data from two published genome-wide associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Fourthly, gene-gene and gene-environment interactions were not analyzed. Additionally, some other important genes, such as ATM gene of DNA-damage sensing [27], ATG16L2 gene related to autophagy [28], and RUNX3 [29] gene in the methionine metabolic pathway that have been reported to be associated with the outcomes of NSCLS, were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, gene-gene and gene-environment interactions were not analyzed. Additionally, some other important genes, such as ATM gene of DNA-damage sensing [27], ATG16L2 gene related to autophagy [28], and RUNX3 [29] gene in the methionine metabolic pathway that have been reported to be associated with the outcomes of NSCLS, were not included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition to pathological staging, which serves as the most important prognostic indicator, several factors are of clinical significance for the evaluation of efficacy of platinum-based adjuvant chemotherapy and prognosis, including gene polymorphisms. 13 Furthermore, the licensing of nivolumab and pembrolizumab in mainland Chinabrought new options for patients with advanced NSCLC. 14 PDL1 is one of the most important biomarkers for PD1/PDL1 inhibitors, and indications are that the higher the expression level of PDL1, the better the efficacy of PD1/PDL1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that methionine biosynthetic process is related to cancer, as many kinds of cancer cells require exogenous methionine to survive 24 . The abnormal dependence of cancer cells on methionine leads to methionine limitation as a potential treatment strategy 25 . Serine, as an important one-carbon donor of the folic acid cycle, can play an antioxidant role because many kinds of cancer cells are highly dependent on it 26 .…”
Section: Changes In the Urine Proteome In Patients With Advanced Lungmentioning
confidence: 99%